CLINICAL EFFICACY OF DRUG VYAN UTKSHEPAHARA GHAN VATI (KALPIT YOG) IN HYPERTENSION - Gupta, Manoj Kumar (Innoriginal: International Journal of Sciences, 2014)
Due to the unwholesome diet, sedentary life style, day by day our country is facing the increasing burden of the patients of high blood pressure, diabetes and obesity. Our country is becoming the capital of these diseases. These diseases mostly treated by allopathic medicines which are having considerable side effects and could not be used on long term basis. So conclusion is that in these disease, the dose of allopathic medicines and disease gradually progresses and in addition due to the side effects of allopathic medicines, it is better that these diseases should be treated by Ayurvedic medicines. In this clinical trial 90 patients of hypertension were randomly selected and divided in to three groups. In Group A Vyan Utkshepahara Ghan Vati , In Group B Atenolol 50 mg and In Group C placebo drug had given to the patients. In all these three groups, group A was found as the most benefited because it showed significant as well as highly significant changes in symptoms and Biochemistry investigations. Whereas Group B (control group) showed significant as well as highly significant changes in symptoms but not in Biochemistry investigations. Placebo showed insignificant changes in both.